Strategy to Promote Student’s Reading and Writing Skills in Small Schools under Bangkok Metropolitan Administration - Kessuwan, Piyatida; Meepan, Supalax (ASEAN Journal of Education, 2024)
The objectives of this research were to achieve three main goals: 1) to investigate the reading and writing conditions of students in small schools under the Bangkok Metropolitan Administration, 2) to analyze factors influencing these conditions and develop strategies to promote reading and writing skills, and 3) to evaluate the suitability and feasibility of these strategies in small schools under the Bangkok Metropolitan Administration. The research employed reading and writing evaluations, interviews, and questionnaires as instruments. The findings revealed that 1) result of the literacy and writing skills of most students were at a fair level, with more than 50 percent showing improvement. 2) the factors affecting students’ literacy in the Thai language were generally at a high level. When considering each factor individually, it was found that the school factors and environmental factors had the highest average impact, followed by the influence of teachers. Strategies to promote student’s reading and writing skills in small schools under Bangkok Metropolitan Administration consist of four main strategies as follows: 1) management that facilitates the development of reading and writing, 2) enhancement of learning management to improve reading and writing, 3) development of technology and learning resources to support literacy, and 4) collaboration in developing reading and writing skills. The first strategy includes 7 strategies and 8 goals, the second strategy includes 5 strategies and 5 goals, the third strategy includes 3 strategies and 3 goals, and the fourth strategy includes 3 strategies and 3 goals. The overall appropriateness of the strategies to promote literacy skills in students was rated at the highest level.